The regression of the bovine tuberculin reaction: Results from the Reactor Quality Assurance study in Northern Ireland. (June 2021) - Courcier, Emily; Ascenzi, Enzo; Gordon, Alan; Doyle, Liam; Buchanan, John; Ford, Tom; Dunlop, Mervyn; Harwood, Roly; McAllister, Kate; McGuckian, Paddy; Kirke, Raymond; Ayastuy, Felipe; et al.
Highlights: Bovine tuberculosis can be detected by comparative intradermal cervical test (CICT). Responses to bovine vs. avian tuberculin purified protein derivative (PPD) were tested. Bovine tuberculin reaction regression in CICT reactors was studied. Regression was correlated with interferon (IFN)-γ and the presence of visible lesions. This enabled identification of atypical herd breakdowns for further investigation. Abstract: Tuberculin skin tests remain widely used in the control of bovine tuberculosis (bTB) in cattle. Little is known about the rate of regression of tuberculin reactions after the comparative intradermal cervical test (CICT) in cattle. This study aimed to collect data to describe tuberculin regression in reactors following the CICT at 72 ± 4 h post injection. Reactors were also tested using the interferon gamma (IFN-γ) assay to establish if any pattern existed between these results and the CICT reaction regression. The data were derived from 108 herds, 112 herd-level CICTs and 1008 animals. A multivariable linear mixed model was built to explore the regression of the bovine tuberculin reaction over time and the influence of potential predictors. The results confirmed a proportional decline in the bovine tuberculin reaction occurred over time. The predictors in the final model demonstrated that regression of the tuberculin reaction differed between reactors according to their IFN-γ test results and whether visible lesions were present at slaughter. Follow-up measurement of tuberculin reactions and the serial use of the IFN-γ assay in large breakdowns has the potential to provide both a mechanism for quality assurance of the current CICT bTB surveillance and the identification of atypical breakdowns or reactors requiring further investigation.